2020
DOI: 10.1109/lra.2020.2966414
|View full text |Cite
|
Sign up to set email alerts
|

Learning Robust Control Policies for End-to-End Autonomous Driving From Data-Driven Simulation

Abstract: In this work, we present a data-driven simulation and training engine capable of learning end-to-end autonomous vehicle control policies using only sparse rewards. By leveraging real, human-collected trajectories through an environment, we render novel training data that allows virtual agents to drive along a continuum of new local trajectories consistent with the road appearance and semantics, each with a different view of the scene. We demonstrate the ability of policies learned within our simulator to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 27 publications
0
77
0
Order By: Relevance
“…For both robots and autonomous cars, training and testing AI in virtual environments has emerged as a unique solution. It is reported that both robots and autonomous cars, without any prior knowledge of the task, can be trained entirely in virtual environments and successfully deployed in the real world (Amini et al, 2020…”
Section: Robots and Autonomous Carsmentioning
confidence: 99%
“…For both robots and autonomous cars, training and testing AI in virtual environments has emerged as a unique solution. It is reported that both robots and autonomous cars, without any prior knowledge of the task, can be trained entirely in virtual environments and successfully deployed in the real world (Amini et al, 2020…”
Section: Robots and Autonomous Carsmentioning
confidence: 99%
“…Chen et al [28] developed a deep Monte Carlo Tree Search (deep-MCTS) control method for vision-based autonomous driving for predicting driving maneuvers to assist in enhancing the stability and performance of driving control. Amini et al [29] introduced a data-driven simulation and training engine capable of learning end-to-end autonomous vehicle control policies using only sparse rewards for allowing virtual agents to drive along a continuum of new local trajectories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, end2end learning is defined as developing and training a complex neural network to directly map input sensory data to vehicle commands [ 10 ]. The authors of Reference [ 11 ] present an end-to-end imitation learning system for off-road autonomous driving by using only low-cost onboard sensors, having their DNN policy trained for agile driving on a predefined obstacle-free track.…”
Section: Related Workmentioning
confidence: 99%